Reinforcement of Polymer Nano-Composites: Theory, Experiments and Applications - Vilgis, T (Cambridge University Press, 2013)
Why a new book about the science of an apparently old material? This question can be easily posed, when reading the title of this book. Indeed, filled rubbers are well known and well used in daily life. However, it is less known that recipes and the corresponding processing cycles of carbon black or silica filled rubber are extremely complex, which leads to a complex structure of the material in a wide range of length scales. Rubbers are classes of relatively soft materials without which modern technology would be unthinkable, similar to the case of metals, fibres, plastics, glass, etc. No matter where these rubber materials find their application, especially in tires and in a great variety of industrial and consumer products, e.g. motor mounts, fuel hoses, heavy conveyor belts, profiles, etc., the applications make high demands on rubber materials